A Study Of Reflective Practice Within A Multidisciplinary Team In An Elite Football Academy - Shree Sharman; Umidbek Axunov; Masooma Al Balushi (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: this research intends to explore how reflective practice is being perceived and applied within an elite English football academy setting. Specifically, it aims to investigate how key staff, working as part of a multidisciplinary team (MDT), interpret and implement The FA’s Plan-Do-Review model. Furthermore, how do academies mobilise reflective practice according to the values and unique cultural environment of the Club under the auspices of the Premier League’s Elite Player Performance Plan (EPPP). Methodology: The study used a qualitative approach with semi-structured interviews involving twelve MDT members. Moon’s Model of Reflection and The FA’s Plan-Do-Review framework guided thematic analysis using manual coding. Main Findings: Findings indicate that 1) There is a disconnect between the understanding and learning of reflective practice through coach education courses and its application within the real world. 2) Reflective practice should be nurtured and developed through strong networks and interprofessional collaboration, utilising communities of practice and mentoring relationships both in and outside the work environment. 3) The different disciplines working within an MDT will engage in reflection to varying depths and levels. Rather than viewing reflection on a hierarchical scale, the level and method of reflection should be determined by the individual, their experiences, and the context. Novelty/Originality of this study: This study provides empirical insight into real-world reflective practice among sports professionals, offering a novel multidisciplinary perspective and practical recommendations for coach education and academy policy.